A Novel Method of Determining Portal Systemic Shunting using Biodegradable 99TCm Labelled Albumin Microspheres. Issue 4 (1995) - Yates, J.; Nott, D. M.; Maltby, P. J.; Billington, D.; Baxter, J. N.; Shields, R.; Jenkins, S. A.
Abstract : Portal systemic shunting (PSS) and portal pressure were measured in control rats and in animals with portal hypertension induced by partial portal vein ligation (PPVL). The portal pressure in rats with partial portal vein ligation (13.4 ± 0.5 mm.Hg.) was significantly higher ( p < 0.005) than in the control group (9.6 ± 0.6 mm.Hg.). Portal systemic shunting measured by consecutive injections of radiolabelled methylene diphosphonate (MDP), a non-diffusable marker and albumin microspheres directly into the splenic pulp was significantly increased ( P < 0.005) in the portal hypertensive animals (30.8 ± 2.5%) compared to sham operated rats (2.6 ± 1.5%). Similarly, in portal hypertensive rats portal systemic shunting measured by intrasplenic injections of radiolabelled cobalt microspheres (37.1 ± 3.9%) was significantly greater ( p < 0.005) than in control animals. There was a good correlation and agreement ( r = 00.97) between the two methods of measuring portal systemic shunting. However because the 99 Tc m -albumin microspheres are biodegradable the method allows portal systemic shunting to be measured in man. Furthermore since the computer adjusts the baseline to zero after each determination of portal systemic shunting the methodology allows repeated measurements to be made.